Supervisor perspectives on the 'end-stage' of the doctoral examination process. Issue 2 (23rd February 2022) - Dally, Kerry; Holbrook, Allyson; Lovat, Terence; Fairbairn, Hedy
ABSTRACT: There has been substantial research on doctoral supervision and examination, yet rarely a focus on what happens at the end-stage of the process when examiner feedback is received and addressed. This article reports survey findings ( n  = 262) from a study investigating supervisor perceptions about Australian end-stage doctoral examination processes. In general, supervisors believed that existing university processes were satisfactory, with the caveat that, at times, there was undue variability between examiners, or difficult-to-reconcile committee decisions about the outcome. Supervisors generally identified that revisions and the preparation of the response-to-examiner report was a 'shared responsibility'. While supervisors strongly agreed that graduates achieve doctoral level in terms of substantive knowledge, they were less sanguine about their research autonomy. This impression was compounded if candidate input into the decisions about examiner comments was undervalued or if there was no direct avenue of response by the candidate.